(untitled) (Research, Society and Development, 2022)
Spinal muscular atrophy (SMA) is a genetically-caused muscular hypotonia that can be screened through neonatal screening. Screening for the disease became recommended in 2019 by the American Panel on Traceable Diseases in Childhood, for this reason this work seeks data in the scientific literature on spinal muscular atrophy and its screening in neonatal screening. The BVS, American Academy of Pediatrics and PubMed databases were used for the research, with a total of 26 selected. We found 4 countries with a pilot project for SMA screening, which used the qPCR test for screening. Asymptomatic children who were diagnosed with SMA by genetic testing and who started treatment at most 2 months of age achieved age-appropriate neuropsychomotor development, were able to sit and walk. Based on this, we conclude that early SMA screening and early treatment initiation are capable of modifying the natural history of the disease and giving children with this disease the opportunity to have age-appropriate motor development.